The Ethics of the US Business Executive: A Study of Perceptions - Stevens, B. (Journal of business ethics, 2004)
Gallup Polls have reported on the perceived ethics of various professions in the US since 1976. Clergymen and pharmacists were consistently identified as two of the most ethical professionals in the 1980's and 1990's. Business executives have not fared well in these polls and have not been rated among the top ten most ethical professions in any of the years the poll was taken. Ethical codes have not done much to belay the perception that the US business executive is not very ethical. Whether the Sarbanes-Oxley Act will impact the ethical behavior of business executives remains to be seen.